2015
DOI: 10.1016/j.joca.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Hidden osteophyte formation on plain X-ray is the predictive factor for development of knee osteoarthritis after 48 months – data from the Osteoarthritis Initiative

Abstract: Knees with osteophyte formation at the IC, even those of K/L severity grade 0/1, are at risk for the development of radiographic OA by 48 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…Our findings from the current longitudinal study were consistent, with OPs detected only by MRI but not by X-ray (MRI-OPs) being associated with increases in cartilage defects/loss and subchondral bone abnormalities over time. Our results are largely in line with findings from a previous case-control study which reported that hidden OPs on plain X-ray at femoral inter-condylar notch were at risk for the development of ROA after 48 months 37 , indicating MRI-OPs can serve as a biomarker for knee osteoarthritic structural progression before radiographic changes become evident.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings from the current longitudinal study were consistent, with OPs detected only by MRI but not by X-ray (MRI-OPs) being associated with increases in cartilage defects/loss and subchondral bone abnormalities over time. Our results are largely in line with findings from a previous case-control study which reported that hidden OPs on plain X-ray at femoral inter-condylar notch were at risk for the development of ROA after 48 months 37 , indicating MRI-OPs can serve as a biomarker for knee osteoarthritic structural progression before radiographic changes become evident.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, magnetic resonance imaging (MRI) is a non-invasive multiplanar tomographic modality that can assess many knee osteoarthritic changes [ 9 ]. Studies suggest that MRI can assess OPs with much greater sensitivity than radiographs and in locations that are not easily visualised by conventional radiography due to its ability to provide three-dimensional information [ 10 12 ]. Our recent study reported that MRI-detected OPs are highly prevalent in older adults (85% vs 10% radiographic OPs prevalence) and can independently and site-specifically predict increases in cartilage defects, BMLs and loss of cartilage volume, and worsening knee pain over time, suggesting MRI-detected OPs are clinically relevant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a non-invasive multiplanar tomographic tool that has been introduced to evaluate knee osteoarthritic changes such as bone marrow lesions (BMLs) 9 , cartilage defects 10 and cartilage volume 11 . Although MRI can assess OPs in locations that are not easily visualised by conventional radiography 12,13 , and at greater sensitivity than radiographs for detection of early formation of OP 14 , few data are available to compare the prevalence of OPs detected by MRI and radiography in population-based samples. It has been shown that greater size of MRI-detected OPs correlated with higher KellgreneLawrence score 15 and increased knee pain 16 , and cross-sectional studies have suggested that increasing size and presence of MRI-defined OPs was associated with severity of knee OA 15,17,18 as well as presence of pain.…”
Section: Introductionmentioning
confidence: 99%